Corporate risk disclosure: evidence of Shari'ah compliant companies in Malaysia / Noridayu Abdullah Sani - Abdullah Sani, Noridayu (2011)
An increase in corporate failure in the global market resulted in an increase in demand on risk disclosure by the market participants. Owing to the rule of full disclosure in Islamic accounting, Shari'ah compliant companies need to increase the quality of corporate disclosure to maintain investors' confidence towards the benefits of Shari'ah principles in protecting their investment returns that include information on business risks. For Shari'ah compliant companies, Shari'ah stock screening criteria involves investment screening based on qualitative and quantitative tools that will result in the selection of Shari'ah compliant companies and removal of Shari'ah non-compliant companies. The main objective of this study is to examine the influence of corporate risk disclosure on companies' performance. The second objective is to examine the moderation effect of the screening criteria (FTSE Bursa Malaysia EMAS Shari 'ah Index and FTSE Bursa Malaysia Hijrah Shari'ah Index) on the relationship between CRD and companies' performance. The analysis reveals that there is significant negative relationship between the CRD and companies' performance. This indicates that an improvement in companies' performance is not a factor to encourage company to release more information on business risks. FTSE Bursa Malaysia EMAS Shari'ah Index and FTSE Bursa Malaysia Hijrah Shari'ah Index do not have an interactive influence on the relationship between corporate risk disclosure and companies' performance.